2010
DOI: 10.1002/sia.3327
|View full text |Cite
|
Sign up to set email alerts
|

Pt2 + , 4+ ions in CeO2 rf‐sputtered thin films

Abstract: . XPS showed formation of cerium oxide with completely ionized species Pt 2+,4+ embedded in the film. The Pt 2+ /Pt 4+ ratio depends on the deposition angle and increases in the case of the film deposition on the MWCNTs. This behavior was explained by the dependence of the polycrystalline film grain morphology on a deposition angle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 13 publications
2
18
0
Order By: Relevance
“…Recent research showed that a simultaneous radio‐frequency (RF) sputtering of CeO 2 and a noble metal can be used for deposition of thin films in a form of a solid solution . Our preliminary experiments showed that Rh–Ce–O thin films prepared by the same method contain rhodium in Rh 3+ and cerium mostly in Ce 4+ oxidation states, which is in good agreement with materials prepared by wet deposition techniques .…”
Section: Introductionsupporting
confidence: 77%
See 2 more Smart Citations
“…Recent research showed that a simultaneous radio‐frequency (RF) sputtering of CeO 2 and a noble metal can be used for deposition of thin films in a form of a solid solution . Our preliminary experiments showed that Rh–Ce–O thin films prepared by the same method contain rhodium in Rh 3+ and cerium mostly in Ce 4+ oxidation states, which is in good agreement with materials prepared by wet deposition techniques .…”
Section: Introductionsupporting
confidence: 77%
“…c. On the other hand, the intensity of the Si 3+ state increases rapidly above 500 K. Figure d shows a Ce 3+ /Ce 4+ ratio calculated from fitting HXPS Ce 3 d spectra, which can give a comparable information about the oxidation states in cerium oxide as the DCe 3+ /DCe 4+ ratio. Increase of a concentration of Ce 3+ ions above 500 K is apparent from Figure d.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…[24,25,[33][34][35][36][37] Av ariety of platinum states is formed through as trongc hemical interaction with the support (SMSI effect), so that platinum can be in cationic states and in different metallicc luster species. [37][38][39][40][41][42][43][44][45] The interaction of metallic platinum particlesw ith ceria, studied in many publications,w as shown to increase the catalytic activity per platinum atom in comparison, for example, with the Pt/Al 2 O 3 catalyst. [16,[46][47][48][49] In this connection, when studying catalytic properties of Pt/CeO 2 systems, it is interesting to uncover the relation of activity with the Pt-CeO 2 interaction strength and to characterizep latinum speciest hat are formed by this interaction.…”
Section: Introductionmentioning
confidence: 99%
“…Pt/CeO 2 thin films show significant catalytic activity towards methanol electrooxidation and high activity in polymer electrolyte membrane fuel cell as anode material . Previous studies on Pt/CeO 2 thin films have demonstrated the presence of Pt 4+ species in the film grown on Si substrate, and Pt 0 and Pt 2+ in the film deposited on indium tin oxide coated glass substrate, whereas both Pt 2+ and Pt 4+ species are observed in the film grown on carbon nanotube . This suggests that substrates influence the oxidation states and concentration of Pt species in Pt/CeO 2 films.…”
Section: Introductionmentioning
confidence: 86%